The Effect of Participative Leadership, Compensation and Job Satisfaction on Performance of Employees of PT. Gemilang Mekar Persada Tangerang - Asep Qustolani; Zenia Azhar Reviani (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Everyone has their own unique traits, habits, thoughts, and desires, and human resources are one of the most important assets of a business. Therefore, expert management is needed to ensure that all stakeholders work together to achieve a common mission to improve employee performance. This study aims to determine the effect of participative leadership, compensation and job satisfaction on employee performance partially. The research method used is using a descriptive verification approach using a survey method. The population in this study were employees of PT Gemilang Mekar Persada with a sample of 86 people with saturated sampling technique. The analytical tool in this study is multiple linear regression analysis, model feasibility test, classical assumption test, coefficient of determination, hypothesis test (statistical t test). The results showed that participative leadership has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance and job satisfaction has a positive and significant effect on employee performance.